Long-term cellular and humoral responses to SARS-CoV-2 vaccinations in patients with solid malignancies undergoing chemotherapy - Liu, Andrew; Necela, Brian; Li, Zhuo; Cogen, Davitte; Wieczorek, Mikolaj A.; Mummareddy, Ashita; Acampora, Marites; Reynolds, Gina A.; Advani, Pooja P.; Moreno-Aspitia, Alvaro; Swift, Melanie D.; Virk, Abinash; et al. (Frontiers in Immunology, 2026)
BackgroundWhile SARS-CoV-2 vaccines are highly effective in healthy individuals, the magnitude and durability of humoral and cellular responses in patients with solid malignancies receiving chemotherapy remain understudied. Previous reports suggest that patients with cancer may not mount adequate immune response after SARS-CoV-2 vaccination. Additionally, most studies focused on humoral responses, while data regarding cellular immune responses are scarce. In this study, we evaluated humoral and cellular responses in patients with solid tumors receiving chemotherapy compared to healthy individuals up to one year after vaccinations.MethodsPatients aged ≥18 who were willing to receive the SARS-CoV-2 vaccine were enrolled. Anti-SARS-CoV-2 immunoassays were used to detect antibodies against nucleocapsid and spike proteins. Human IFN-γ Fluorospot assay was used to determine antigen−specific T-cell responses. Data were compared between groups using Mann−Whitney test for continuous variables and Fisher’s exact test for categorical variables.ResultsA total of 67 subjects (47 patients with cancer and 20 healthy individuals) were included. 1–3 months following the second vaccine doses, 96% of patients with cancer and 100% of healthy individuals demonstrated a positive humoral response. While the positivity rate was not significantly different, patients with cancer had significantly lower spike IgG antibodies than healthy individuals. However, this difference diminished at 6 months when patients with cancer had increased antibodies compared to decreased antibodies in the healthy cohort and no difference was noticed at 12-month. Patients with cancer developed a similar antigen-specific T-cell response as healthy individuals at 1–3 months, 6 months and 12 months. There were no significant differences when comparing patients aged ≤ 55 years vs. >55 years, stages I-III vs. IV, single vs. multiple chemotherapy, and BNT162b2 vs. mRNA-1273 vaccines. There was a significant moderate correlation between neutralization and antibody levels at 12 months. However, despite patients with cancer having a significantly higher COVID risk score, there were no significant differences in COVID-19 infection and hospitalization between patients with cancer and healthy individuals.ConclusionDespite initial impaired antibody responses to SARS-CoV-2 vaccinations, patients with solid malignancies receiving chemotherapy effectively generated long-term cellular and humoral responses by 6 and 12 months, leading to similar infection and hospitalization rates compared to healthy individuals.